The Effect of Collaborative Learning on Academic Motivation - Loes, Chad N. (Teaching and Learning Inquiry, 2022)
This paper explores the effect of collaborative learning on academic motivation among students from 17 institutions throughout the United States. Even in the presence of a wide array of potential confounders, collaborative learning exerted a statistically significant and positive influence on students’ academic motivation levels across four years of undergraduate education. Tests for the presence of interaction effects suggest that the relationship between collaborative learning and academic motivation is similar for all students, regardless of racial or ethnic background.